A Quantitative Study on the Influence of Authenticity and Employee Helpfulness on Customer Delight at The Balcone Hotel & Resort - Safitri Firdaus; Youmil Abrian (Pt. Threeple Herphi Educate, 2025)
This study investigates the influence of authenticity and employee helpfulness on customer delight in the context of a luxury hospitality environment. Using a quantitative, causal-associative approach, the research was conducted at The Balcone Hotel & Resort Bukittinggi, with data collected from 90 guests using a structured questionnaire. The variables measured include authenticity (uniqueness, concept consistency, and staff sincerity), employee helpfulness (responsiveness, problem-solving, and attentiveness), and customer delight (satisfaction, exceeded expectations, and willingness to recommend). Multiple linear regression analysis revealed that both authenticity (β = 0.270, p = 0.002) and employee helpfulness (β = 0.670, p = 0.000) have significant positive effects on customer delight. Furthermore, the F-test confirmed a significant simultaneous influence of the two variables. These findings highlight the importance of integrating authentic service design with emotionally responsive staff behavior to create memorable guest experiences. The study provides theoretical insights and practical implications for hotel managers aiming to achieve emotional differentiation and customer loyalty in competitive hospitality markets.